Dairy activity in family farming in Minas Gerais, Brazil: production costs and cost-effectiveness analysis - Santos, César Correia (2018)
The aim of this study is to analyze and compare the cost-effectiveness of three family dairy farms, located in the municipality of Limeira do Oeste, MG, Brazil, as well as to identify the break-even points and the factors that most influenced the final costs, and their impacts on each property. The analyzed data comprised the period from May 2015 to May 2016 and were collected using forms developed by EMATER-MG (Technical Assistance and Rural Extension Company of the State of Minas Gerais) and MDA (Ministry of Agrarian Development). Gross and net margins as well as results (profit or loss) were considered as cost-effectiveness indices. It was realized that the dairy activity in the properties studied exhibited low efficiency in the use of inputs, implying idle productive capacity, an increase in the proportion of fixed costs in the composition of total costs, and low productivity per animal per unit area. Therefore, diary activity was highly dependent on the sale of animals in order to afford and present positive results. Among the components of the effective operating cost, feeding is the most representative (averaging 63.09%), in the three studied properties, being the tax rates considered as fixed (9.41%) and miscellaneous expenses (9.49%) also expressive. The properties showed high fixed costs and break-even points; in one property, these could not be determined as the unit variable cost was higher than the average selling price in the market. In the economic analysis, the three systems showed positive net margins and results, indicative of production viability in the long term.